Novel difluoromethyl-containing 1-((4-methoxy-3-(piperazin-1-yl)phenyl)sulfonyl)-1H-indole scaffold as potent 5-HT6R antagonists: Design, synthesis, biological evaluation, and early in vivo cognition-enhancing studies. (15th September 2022) - Yi, Chao; Xue, Yaping; Chen, Kangzhi; Wang, Tao; Yu, Jiahui; Wang, Zusheng; Jin, Chuanfei
Graphical abstract: Highlights: Novel difluoromethyl-containing indole scaffold as 5-HT6 R antagonists. Compound C14 showed10 folds higher 5-HT6 R affinity than idalopirdin in vitro . Compound C14 exhibited good in vitro metabolic properties. Compound C14 showed good cognition-enhancing property in vivo . Abstract: Herein, a series of novel 1-((4-methoxy-3-(piperazin-1-yl)phenyl)sulfonyl)- 1 H -indole derivatives were designed and synthesized via hybridization strategy of idalopirdine and SB-271046. The optimal compound C14 (Ki = 0.085 nM), with difluoromethyl on C3 position on indole scaffold, increased the affinity for the 5-HT6 R up to 10-folds than idalopirdine (Ki = 0.83 nM). Additionally, C14 had good pharmacokinetic properties and in vitro metabolic properties. Finally, C14 could efficiently reverse the scopolamine induced emotional memory deficits in novel object recognition assay in rats. Thus, we propose C14 might be considered as a new cognition-enhancing agent and the further studies are now underway in our laboratory.